2014
DOI: 10.1186/s12968-014-0078-9
|View full text |Cite
|
Sign up to set email alerts
|

Vortex flow during early and late left ventricular filling in normal subjects: quantitative characterization using retrospectively-gated 4D flow cardiovascular magnetic resonance and three-dimensional vortex core analysis

Abstract: BackgroundLV diastolic vortex formation has been suggested to critically contribute to efficient blood pumping function, while altered vortex formation has been associated with LV pathologies. Therefore, quantitative characterization of vortex flow might provide a novel objective tool for evaluating LV function. The objectives of this study were 1) assess feasibility of vortex flow analysis during both early and late diastolic filling in vivo in normal subjects using 4D Flow cardiovascular magnetic resonance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(147 citation statements)
references
References 44 publications
9
138
0
Order By: Relevance
“…Three-dimensional (3D) time-resolved phase-contrast MRI with three-dimensional motion encoding permits flow assessment of the true 3D nature of intracardiac blood flow over the cardiac cycle (12)(13)(14)(15)(16)(17). A recent 4D (3D + time) flow MRI study of the normal RV described patterns and energetics of RV flow with a special emphasis on RV diastolic inflow passing directly to ensuing outflow (Direct Flow).…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) time-resolved phase-contrast MRI with three-dimensional motion encoding permits flow assessment of the true 3D nature of intracardiac blood flow over the cardiac cycle (12)(13)(14)(15)(16)(17). A recent 4D (3D + time) flow MRI study of the normal RV described patterns and energetics of RV flow with a special emphasis on RV diastolic inflow passing directly to ensuing outflow (Direct Flow).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, 30 healthy controls within a similar age range and without history of cardiac disease were included. Patients and volunteers in this study were also included in a study reporting on quantification of flow over the left atrioventricular valve, 4 vortex core analysis, 15 and quantification of regurgitation. 16 Patients underwent echocardiography, and echocardiogram details were analyzed.…”
Section: Study Populationmentioning
confidence: 99%
“…However, it was able to be shown that vortex flows can occur at non-physiological sites in various diseases. Aneurysms, pulmonary hypertension, and various heart diseases correlate with the occurrence and the intensity of vortex flows [18,19]. In addition, various valve pathologies and the use of artificial heart valves result in different vortex flows [20].…”
Section: Vortex Flowsmentioning
confidence: 99%